Increased thyroxine levels of patients with allergic rhinitis - Violeta Lokaj-Berisha; Besa Gacaferri Lumezi (Scientific Reports)
Abstract Allergic rhinitis and asthma are common respiratory conditions with complex etiologies involving genetic, environmental, and physiological factors. In these conditions, the role of thyroid function remains underexplored. This study enrolled 116 participants with a mean age of 29.55 years: 66 with allergic rhinitis, 20 with concomitant asthma, and 30 healthy controls. BMI and serum IgE, T3, T4, and TSH levels were measured. A significant familial history of atopy was reported by 66.4% of participants. Skin prick tests revealed predominant sensitivity to house dust mites (55.2%). BMI was within normal ranges across all groups, serum IgE levels were significantly elevated in patients with respiratory allergies compared to controls (Mean = 36.85 IU/mL), especially those with allergic rhinitis and concomitant asthma (Mean = 218 IU/mL). Significant differences in serum T4 levels were observed, particularly among those with allergic rhinitis (p < 0.001 and p < 0.05). Pearson correlation analysis revealed significant associations between age, BMI, and thyroid hormones, with notable sex-specific differences (p < 0.05 and p < 0.01). The study highlights the complex interplay between metabolic, endocrine, and immune responses in respiratory allergies. Elevated serum IgE levels and alterations in thyroid function, particularly among males, suggest potential pathways for targeted therapeutic interventions. Further research is needed to elucidate these relationships and their underlying mechanisms.